6 - Globalisation, Institutional Arrangemen Poverty in Rural Cameroon: 10.4314/ad.v28i2.22179 - Baye , Francis Menjo (Africa Development, 2003)
This paper posits that the institutional environment, which is constantly modi fied by the forces of globalisation, significantly influences access to and returns on primary assets that determine poverty outcomes in rural societies. Within the framework of institutional economics related to globalisation, rural institutions and poverty, the paper ( 1 ) identifies monetary and exchange rate arrangements, public debt burden, democratic culture and rent-seeking, openness and obsta cles to international trade, economic and structural reforms, and NGO activities as the main channels by which the forces of globalisation permeate down to the rural poor and (2) considers changes in land tenure arrangements, rural financial markets and marketing of agricultural products as important within the institu tional environment that determines the capacity of rural dwellers to build on and derive returns from their primary asset endowments. Good governance is viewed as crucial in curbing socio-economic difficulties and poverty in rural Cameroon.